Pengaruh Variasi Sudut Kemiringan Bilah terhadap Efisiensi Turbin Angin Sumbu Horizontal (HAWT) Berdiameter 500 mm untuk membangkitkan generator listrik DC 5-24 Volt - toro, Widyan (Motor Bakar : Jurnal Teknik Mesin, 2025)
The increasing demand for energy has led to a growing dependency on fossil fuels, contributing to carbon dioxide (CO₂) emissions and environmental pollution. Wind energy is one of the renewable energy alternatives that is environmentally friendly and sustainable. This study aims to investigate the effect of blade tilt angle variations on the efficiency of a 500 mm diameter horizontal axis wind turbine (HAWT) made of wood, combined with a DC electric generator. The experimental method involved measuring voltage, current, and output power at various blade tilt angles (10° to 40°). The results indicate that the highest energy conversion efficiency occurs at a tilt angle of 15°, with an efficiency of 2.04%. Although the output power increased at higher tilt angles, the efficiency decreased due to the imbalance between input mechanical power and output electrical power. Therefore, a tilt angle of 15° is recommended as the optimal angle for the operation of this turbine-generator system to achieve maximum energy conversion efficiency